The development of a multidimensional meaning of tax: From unfair tax to fair. Issue 1 (February 2023) - Hilling, Axel; Sandell, Niklas; Sonnerfeldt, Amanda; Vilhelmsson, Anders
Historically, companies have communicated taxes as a burden, as the benefits provided by governments are not perceived to be in proportion to their payments. With sustainable development becoming central in many policy areas, new discourses including 'fair' or 'sustainable' tax have become omnipresent in public talk on taxes. This paper analyzes tax discourses in corporate annual reports within this changing context to examine the use of language in the construction of the meaning of tax. By analyzing tax reporting by a state-owned multinational company over two decades, we observe that the communication of taxes increased in both number and types of discourses. Importantly, this highlights the shift in tax discourses from one dominated by codified accounting discourse reinforcing the monolithic representation of tax as an unfair expense, to one where tax is given a multidimensional meaning within a broader discursive context, where tax is a meaningful corporate responsibility to society.